The effectiveness of dapsone as refracterial therapy for juvenile dermatomyositis - Susanto, Prayogi Miura (International Journal of Research in Dermatology, 2022)
Juvenile dermatomyositis (JDM) is a rare autoimmune disease that affects mostly children’s muscles and skin. The small number of patients with JDM, heterogeneous disease phenotype, and few clinical trials for JDM pose challenges for clinicians in developing standard treatment protocols. Although there has been some consensus, the obstacles to JDM therapy, especially in refractory cases, have not been resolved. Dapsone is one of the anti-inflammatory agents that can provide significant clinical improvement in patients with dermatomyositis. This aim of the study was to discuss various previous studies to determine the potential use of dapsone in cases of refractory JDM.